Temporalité et aspectualité en anglais : opérations, représentations, cognition - Gilbert Ghio (Corela)
The aim of this article is to link the linguistic operations in the expression of time to the underlying cognitive operations. After establishing a link between spatial and temporal representation it examines the way in which time is conceptualized and represented in language. It then applies its findings to the study of the simple tenses and aspects of English.